Transverse spin in the light-ray OPE - Chang, C-H; Kologlu, M; Kravchuk, P; Simmons-Duffin, D; Zhiboedov, A (Springer Nature, 2022)
We study a product of null-integrated local operators $\mathcal{O}$1 and $\mathcal{O}$2 on the same null plane in a CFT. Such null-integrated operators transform like primaries in a fictitious d − 2 dimensional CFT in the directions transverse to the null integrals. We give a complete description of the OPE in these transverse directions. The terms with low transverse spin are light-ray operators with spin J1 + J2 − 1. The terms with higher transverse spin are primary descendants of light-ray operators with higher spins J1 + J2 − 1 + n, constructed using special conformally-invariant differential operators that appear precisely in the kinematics of the light-ray OPE. As an example, the OPE between average null energy operators contains light-ray operators with spin 3 (as described by Hofman and Maldacena), but also novel terms with spin 5, 7, 9, etc. These new terms are important for describing energy two-point correlators in non-rotationally-symmetric states, and for computing multi-point energy correlators. We check our formulas in a non-rotationally-symmetric energy correlator in $\mathcal{N}$ = 4 SYM, finding perfect agreement.